Weather events and welfare in the Philippine households - Connie B. Dacuycuy (Philippine Institute for Development Studies (PIDS), 2016)
Using fixed effects estimators to remove unobserved heterogeneity and instrumental variable technique to address the endogeneity of income, this paper analyzes the effect of weather events on welfare in the Philippines. It finds that, one, treating income as an exogenous variable underestimates the effect of income on the household's resource allocation. Two, there are more expenditure shares for which income is endogenous using the tropical cyclone data than using the heat index deviation data as instruments. Three, households choose cheaper foods but just as nutritious when they are frequently hit by tropical cyclones. Four, the presence of children affects most of the food items, and it has the biggest effect on non-alcoholic beverages, such as juice and coffee, while the presence of the elderly affects only a few expenditure items, such as education and medical care. Based on the results, specific recommendations are forwarded. In broader terms, the study points to the desirability of greater forms of investment in resilience against weather events and climate change. At the household level, poverty is a binding constraint to good investment in resilience against weather events and the government has to continue its efforts toward poverty reduction. To this end, the government should ensure that the Department of Social Welfare and Development internal and external convergence strategy is successfully implemented.
Keywords: 330; Weather events; Welfare; Fixed effects